Christ as Divine Agent in Paul - Wanamaker, C. A. (Scottish journal of theology, 1986)
E. L. Allen, writing in a little noticed article in 1953, claimed that just as the early Christian Apostles were the representative of Jesus in accordance with the shaliach conception of Rabbinic Judaism, Jesus himself was portrayed as the representative or shaliach of God in a number of New Testament works from the writings of Paul to the Gospel of John. Some fifteen years later, apparently without knowledge of Allen's essay, Peder Borgen examined the representative idea, or the agency idea as he more aptly called it, in Jewish halakhic writings and argued that the long recognized sending motif in John showed close affinities with this material. He went on to argue that the portrayal of Jesus as a ‘heavenly agent who has come down among men’ needed to be understood in terms of Jewish Merkabah mysticism. Merkabah mysticism combined among other things,halakah, heavenly figure and the heavenly world just as the concept of agency does in the Gospel of John. He was also able to show the same phenomena in Philo and suggested that this too must be seen as part of the background for the agency concept in John.